Base excision repair-inspired DNA motor powered by intracellular apurinic/apyrimidinic endonuclease. Issue 3 (3rd January 2019) - Li, Lidan; Li, Na; Fu, Shengnan; Deng, Yingnan; Yu, Changyuan; Su, Xin
Abstract : A DNA motor was operated in living cells by endogenous AP endonuclease. Abstract : The transition of DNA nanomachines from test tubes to living cells would realize the ultimate goal of smart therapeutic dynamic DNA nanotechnology. The operation of DNA nanomachines in living cells remains challenging because it is difficult to utilize an endogenous driving force. Inspired by the base excision repair (BER) process, we demonstrate a 'burnt-bridge' DNA motor system powered by intracellular apurinic/apyrimidinic (AP) endonuclease APE1. The high specificity of APE1 to the AP site in double-stranded DNA permits directional and autonomous movement. The advanced single-molecule fluorescence technique was utilized to directly monitor the stepwise movement of the motor strand, confirming the excellent controllability and processivity of this system. The speed of this DNA motor relies highly on APE1 concentration, allowing discrimination by APE1 level against cancer cells and normal cells. Western blot was used to confirm APE1 expression level. Successful operation of the DNA motor in living cells demonstrates that an endogenous enzyme can operate the rationally designed DNA nanostructures in a programmable way, rather than digesting simple molecular probes. This is useful and practicable for broad application, such as for cellular diagnostic tools, gene regulators for DNA repair, and enzyme-mediated drug delivery.